Mortalitet hos Newfoundland : med fokus på dilaterad kardiomyopati - Knutsson, Matilda (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2010)
Dilated cardiomyopathy (DCM) is the second most common heart disease in dogs. Since the disease is seen more frequently in certain breeds, among them Newfoundland dogs, a genetic factor is suspected. This study was partly undertaken to investigate whether there is a significant sex predilection regarding DCM. Moreover, the difference in mean age of death between male dogs and females with DCM was investigated, as well as males and females dying from DCM compared to dying from other reasons (i.e. without DCM). The most common causes of death in Swedish Newfoundland dogs were elucidated. This study was also undertaken as a part of a European genetic study, with the aim to identify Newfoundland dogs with and without DCM. Two hundred and fifty-four purebred Newfoundland dogs, among them 104 males and 150 females, had been blood sampled during approximately 20 years and information about them was collected retrospectively by means of autopsy reports and telephone interviews. Seventy-one cases of DCM were found. Males were overrepresented. No significant difference regarding the mean age of death between males and females dying from DCM was observed. Bitches dying from DCM were significantly younger than other bitches. No such difference was observed among the male dogs. Apart from DCM, the four most common causes of death among Newfoundland dogs in Sweden were joint- and skeletal related diseases, tumours, senescence and skin disorders.